Strategi Membangun Personal Branding Selebgram di Kabupaten Karawang - Agisti, Dhea; Mayasari, Mayasari; Budhiharti, Tri Widya (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze the personal branding strategies employed by Instagram influencers in Karawang Regency to build and maintain their self-image on the platform. Using a qualitative descriptive approach grounded in the constructivist paradigm, the research identifies four primary strategies utilized by influencers: ingratiation, self-promotion, exemplification, and supplication. Data were collected through in-depth interviews with four influencers who have significant followings and focus on various niches, such as beauty, music, humor, and family life. The findings reveal that ingratiation is employed to create emotional connections with the audience through personal interactions, such as responding to comments and expressing gratitude. Self-promotion is demonstrated by showcasing competence, experience, and knowledge in their respective fields to build a credible and relevant image. Exemplification involves displaying positive values, such as hard work and dedication, which inspire the audience. Meanwhile, supplication includes acknowledging weaknesses and inviting collaboration, which strengthens emotional bonds and fosters an authentic impression. The study concludes that these four strategies complement each other in forming a strong personal brand on social media. Influencers in Karawang Regency have successfully crafted an authentic, relatable, and inspiring self-image through a combination of genuine interactions, relevant content, and a humanized approach. These findings emphasize that personal branding on Instagram relies not only on outward appearances but also on the ability to build close relationships with the audience through honesty, empathy, and positive contributions.